PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT KOLEGA BISNIS INDONESIA JAKARTA SELATAN - Muhammad Dwi Arfiansyah; Nopi Oktavianti (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of the work environment and work motivation on employee performance at PT. South Jakarta Indonesian Business Colleague partially or simultaneously. The research method used was a saturated sample of 60 employees. The data collection technique is by questionnaire, while the data analysis methods used are validity test, reliability test, classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient (R) analysis, coefficient of determination analysis and hypothesis testing. The research results show that there is a partial positive influence between the work environment and employee performance. Where the simple linear regression equation Y= 20.605+0.388X1 means it has a positive effect. The t test is tcount 4.766> ttable 2.002 then H01 is rejected and Ha1 is accepted. The research results show that there is a partial positive influence between the work environment and employee performance. Where the simple linear regression equation Y=20.851 +0.478X2 means it has a positive effect. The t test is tcount 4.926> ttable 2.002 then H02 is rejected and Ha2 is accepted. The research results show that there is a positive influence between work motivation variables and employee performance simultaneously where the multiple regression equation Y=13.550+0.340X1+0.266X2 means a positive effect. The f test is Fcount 19.231> Ftable 3,15884, so H03 is rejected and Ha3 is accepted, meaning that the work environment variables and work motivation have a significant effect simultaneously on employee performance. According to the correlation coefficient, a value of 0.635 is obtained, which is in the interval 0.600 -0.799. This means that the work environment and work motivation have a strong relationship to employee performance. The results of the determination test show that 0.403 if the work environment and work motivation have an effect on employee performance variables.